COVID-19 - Mahbi Maulaya; Nanda Blestri Jasuma (PCD Journal, 2021)
Covid-19 merits a scientific examination from cosmopolitanism, a widely acknowledged, global-nuanced thought. During the pandemic, strong stances of nationalism and xenophobia have been taken, leaving little room for global cooperation in countering the virus, and recognition of human rights has ebbed. Since this reality is opposed to its ideational and normative essence, cosmopolitanism offers its criticisms and proposals. By diving into a cosmopolitan way of thinking, this study criticises the rise of 'health nationalism' in state policies as well as the xenophobia manifested through the blaming of people of Asian—particularly Chinese—heritage for the viral outbreak. Regarding its proposals, cosmopolitanism offers two suggestions: 1) international society must opt to endorse global integration through multilateralism, and 2.) countries should avoid exclusionary health programmes and commit to solidarity-based countermeasures. The underlying arguments of this study are backed by the application of library research and qualitative methods.